Sex estimation of upper long bones by selected measurements in a Radom (Poland) population from the 18th and 19th centuries AD - Tomczyk Jacek (Anthropological Review, 2017)
Several studies have shown that sex estimation methods based on measurements of the skeleton are specific to populations. Metric traits of the upper long bones have been reported as reliable indicators of sex. This study was designed to determine whether the four long bones can be used for the sex estimation of an historical skeletal population from Radom (Poland). The material used consists of the bones of 169 adult individuals (including 103 males and 66 females) from the 18th and 19th centuries. Twelve measurements were recovered from clavicle, humerus, radius and ulna. The initial comparison of males and females indicated significant differences in all measurements (p < 0.0001). The accuracy of sex estimation ranged from 68% to 84%. The best predictor for sex estimation of all the measurements in Radom’s population was the maximum length of the radius (84%), and the ulna (83%), and the vertical diameter of the humeral head (83%). The Generalized Linear Model (GLM) detected the strongest significant relationship between referential sex and the vertical diameter of the humeral head (p < 0.0001), followed by the maximal length of the ulna (p = 0.0117). In other measurements of the upper long bones, GLM did not detect statistically significant differences.